Elgar encyclopedia of European Union public policy - Graziano, Paolo 1971-; Tosun, Jale 1980- (Edward Elgar Publishing, 2022)
"A holistic and extensive exploration of both the dynamic and incremental changes in EU public policy and the decision processes surrounding them, this Elgar Encyclopedia is the definitive reference work in the field of EU public policy. Unifying theoretical insights with empirical phenomena, this pioneering Encyclopedia begins by engaging with the multi-level structure of the EU's polity and identifies how this affects public policy, considering the role of various non-state actors in EU policymaking, and the concepts of Europeanization and policy diffusion. Offering a theoretical introduction to policy integration, it examines intergovernmentalism, neofunctionalism, and postfunctionalism, alongside an innovative analysis of policy styles and the effects of recent crises on EU public policy, including COVID-19 and populism. Chapters conclude by reflecting on policy implementation and dynamics, and the impact of feedback on public policies and institutions. Ultimately demonstrating that the study of public policy in the EU has produced a set of EU-specific analytical perspectives, this timely book will guide further research avenues into EU public policy for students and scholars interested in (EU) public policy, public administration and comparative politics, alongside informing the decision-making of policymakers globally. Key Features: - Accessible format split into 9 thematic parts - Fully cross-referenced with select bibliographies for further reading - Entries written by an international and interdisciplinary group of over 90 preeminent experts in the field of public policy"
Keywords: Europäische Union; Staatstätigkeit; European Union / https://isni.org/isni/0000000123754495; Political planning / European Union countries / Encyclopedias; European Union; Political planning; European Union countries; Encyclopedias; Aufsatzsammlung